Armenian Residents in the Heart of Isfahan - Narciss, M.Sohrabi (2008)
Isfahan is one of the richest and most historical cities of Iran, and Jolfa is located in its southern part which is separated from other parts by the Zayandeh –Roud. Since Joulfa is home for Armenian residents in this region, therefore, it is different from cultural, social and economic viewpoint, Texture By taking into consideration its four-hundred years antiquity, it possesses a series of valuable historical buildings, which has locational – atmospherical-social and cultural advantages. But severity of packed damages on the shell of Jolfa region in recent decade has been so much because of dispersion of single remained buildings that has resulted in defacement of the concept “historical texture” and facing Jolfa region to “form and environmental identification crisis”, but inner values of Jolfa are still so impressive. In recent years different plans in order to renovate and rehabilitate this historical texture have been performed. This article concerns with introduction of Jolfa quarter and plans performed in order to rehabilitate and protect Jolfa region.